Intestinal Spirochetosis mimicking inflammatory bowel disease in children - Helbling Rossana; Osterheld Maria-Chiara; Vaudaux Bernard; Jaton Katia; Nydegger Andreas (BMC, 2012)
Abstract Background Intestinal spirochetosis is an unusual infection in children and its clinical significance in humans is uncertain. The presence of these microorganisms in humans is well-known since the late 1800's and was first described in 1967 by Harland and Lee by electron microscopy. Case presentation This article reports the findings of one pediatric case, review of the current literature, and an overview of therapeutic options. Conclusion A high degree of suspicion is required in cases presenting with abdominal pain, chronic diarrhoea and/or hematochezia associated with a normal endoscopic examination, thus emphasizing the importance of multiple biopsies throughout the colon.